EVALUATION OF THERMAL STORAGE CAPACITIES OF SOME SELECTED MATERIALS FOR SOLAR DRYING APPLICATIONS (FUDMA JOURNAL OF SCIENCES, 2020)
This work aimed at evaluating the thermal storage capacities of granite grits, laterite rock, sand, laterite, and Clay for solar drying applications. The sample materials were ground and sieved through 0.425mm British Standard sieve. The thermal conductivity, specific heat capacity, bulk density and melting point of the materials were determined. The results showed that Clay displayed better potentiality as thermal storage material with the highest thermal conductivity and specific heat capacity of 2.16 W/m oC and 1.398 kJ/kg K respectively. Laterite was observed to be the least with 1.07 W/moC, and 0.499 kJ/kg K respectively. The Sand was observed to have higher bulk density compared with other sample materials while Laterite exhibited the lowest. The analysis of the result indicates that clay could be used as material for thermal energy storage facility in solar drying applications.
Keywords: sensible heat storage, solar-drying application, and thermal-storage capacity